Strategi Pemasaran Produk Animasi PT Ayena Mandiri Sinema - Aldrich Ilyas; Sapta Raharja; Tjahja Muhandri (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
PT Ayena Mandiri Sinema (PT AMS) is one of the tenants (SMEs) fostered by the Incubator Center of Technology (BIT) BPPT, engaged in animation and multimedia. The main problem is when  marketing Intellectual Property (IP) product animation, such as animated film called Super Neli. Animation film. Generally in Indonesia, marketing product animation of IP dominated by large companies both foreign and domestic, and there are also marketing partners which are quite influential. This make PT AMS be unable to compete with large companies, therefore, it is required a marketing strategy that consider mix marketing aspect and consumer preferences. In this study, identification consumer preference Business to Customer using Kano model is done, the result is dominated by one dimensional attributes while consumer Business to Business obtained attribute must be and one-dimensional dominant. So it becomes an opportunity to maintain and improve product quality to compete in the marketing mix. While the IFE and EFE matrix values of the environmental factors are 2.864 and 2.424, indicating that PT AMS in a position of growth/stability. The result of SWOT analysis that considered mix marketing aspect (product, price, promotion and place) are strategies, then evaluated by QSPM resulting priority strategy which is expanding the marketing network products animation with promotion and market penetration through cooperation with the agency.